Duck Tembusu Virus Exhibits Pathogenicity to Kunming Mice by Intracerebral Inoculation - Ti, Jinfeng; Zhang, Min; Li, Zhijie; Li, Xiuli; Diao, Youxiang (Frontiers in Microbiology, 2016)
In this study, Kunming mice were used as the animal models to study the pathogenicity of TMUV. Three groups of 3-week-old female Kunming mice (n=15 mice per group) were infected with the SDSG strain of TMUV in 50μL allantoic fluid (104.8 ELD50/ 0.2ml) respectively by the intracerebral (i.c.), subcutaneous (s.c.) and intranasal (i.n.) routes. The control group (n=15 mice) was inoculated with 50μL sterile phosphate-buffered saline (PBS). Clinical signs, gross and microscopic lesions, viral loads in different tissues, and serum antibody titers were examined and recorded. Kunming mice infected intracerebrally showed typical clinical symptoms, including severe hindlimb paralysis, weight loss and death. Only dead mice presented severe intestinal mucosal edema. No gross lesions were observed in mice sequentially euthanized. However, microscopic lesions in the brain, spleen, liver, kidney and lung were very typical including varying degrees of viral encephalitis, lymphocytes depletion, liver cell necrosis and nephritis, etc. Viral loads in different tissues were detected by the SYBR Green I real-time PCR assay. Viral loads in the brain, liver and spleen were first detected and maintained a longer time, which indicated that these organs may be the target organs of TMUV. The level of viral loads was consistent with the severity of clinical signs and microscopic lesions in different tissues. The neutralizing antibody began to seroconvert at 8dpi. Clinical signs, microscopic lesions, viral loads and serum neutralizing antibodies weren’t observed in other groups. In summary, TMUV can cause systemic infections and death in Kunming mice by i.c., which provides some experimental basis for further study of the significance of TMUV in public health.